Opinion Expression in Hostile Opinion Climate: An Examination of Exposure to Political Hate among Facebook Users in Pakistan - Naila Rafique; Noshina Saleem (Journal of Management Practices, Humanities and Social Sciences, 2021)
This study investigates the prevalence of the spiral of silence on social media regarding political hate speech. The study assumes that social media users estimate opinion climate on Facebook before expressing their opinion, when they are exposed to political hate speech. The research involved a quantitative analysis via survey. The sample comprised of undergraduate students of Political Science and Media & Communication Studies from two universities i.e., International Islamic University, Islamabad, and University of Punjab, Lahore. A total sample of 250 students was drawn through a systematic random sampling technique. Analytical strategies were based on descriptive statistics and regression analysis. Results indicated that most respondents are exposed to online political hate speech. Further, signiϐicant support was also found for applying the spiral of silence in the context of social media.